IMPLEMENTATION OF PROJECT-BASED LEARNING MODEL ON LEARNING OUTCOMES IN DRAWING HEXAGONS AT SMK MUHAMMADIYAH 2 SEMARANG - Rangga Pratama, Aditya; Muhammad Khumaedi (SOSIOEDUKASI, 2026)
This research aims to examine how the Project-Based Learning (PjBL) approach impacts students’ learning outcomes in technical drawing, specifically in constructing hexagons at SMK Muhammadiyah 2 Semarang. Technical drawing is a fundamental competency in vocational education that requires precision, conceptual understanding, and psychomotor skills. However, conventional learning methods often limit student engagement and hinder the development of these competencies. Therefore, an innovative instructional approach is needed to improve learning effectiveness. This study utilized a quantitative experimental approach with a pretest-posttest control group design. It inculed two classes: the experimental group, which received instruction through the PjBL model, taught via conventional methods. Data were collected through psychomotor performance test, which were assessed using a validate rubric. The instruments were tested for validity using Aiken's V, Content Validity Index (CVI), and reliability using Intraclass Correlation Coefficient (ICC). Data analysis included normality, homogeneity, and independent samples t-tests. The finding indicated that the two groups started with similar initial abilities, as confirmed by the pretest t-test (Sig. = 0,842 > 0,05). Following the intervention, the posttest t-test releaved a clear significant difference between them (Sig. = 0,0001 < 0,05), with the experimental class posting a higher average score of 82,32 compared to 73,60 in the control class. From these results, it’s clear that the PjBL model proves more effective at boosting students’ psychomotor skills and comprehension in hexagon drawing. Overall, Project-Based Learning markedly enchances learning outcomes in technical drawing, making it a strong recommendation for vocational education.